Project-Based Learning and Students’ Motivation: Kacem Amine High School as a Case Study - Khamouja, Abdessallam; Elmakryni, Abdelamlek; Lagmidi, Abdelmounim; Elghouati, Azize; Brigui, Hind (International Journal of Language and Literary Studies, 2025)
The learning methods can either increase or decrease students' motivation. Project-based learning is one of the modern learning methods that have been found to create a welcoming and motivating learning environment where learners enthusiastically participate in constructing knowledge on their own. To investigate this in the Moroccan context, the researchers conducted a correlational study to explore the relationship between project-based learning as an independent variable and students’ motivation types as a dependent variable. The twenty students who participated in the experiment were given a project to conduct. The project was related to what they had studied in unit four of the Ticket to English textbook. The results indicate that PBL and students’ motivation are to a greater extent interrelated.